Moderate-intensity rotating magnetic fields do not affect bone quality and bone remodeling in hindlimb suspended rats. - Da Jing; Jing Cai; Yan Wu; Guanghao Shen; Mingming Zhai; Shichao Tong; Qiaoling Xu; Kangning Xie; Xiaoming Wu; Chi Tang; Xinmin Xu; Juan Liu; et al. (PLoS ONE, 2014)
Abundant evidence has substantiated the positive effects of pulsed electromagnetic fields (PEMF) and static magnetic fields (SMF) on inhibiting osteopenia and promoting fracture healing. However, the osteogenic potential of rotating magnetic fields (RMF), another common electromagnetic application modality, remains poorly characterized thus far, although numerous commercial RMF treatment devices have been available on the market. Herein the impacts of RMF on osteoporotic bone microarchitecture, bone strength and bone metabolism were systematically investigated in hindlimb-unloaded (HU) rats. Thirty two 3-month-old male Sprague-Dawley rats were randomly assigned to the Control (n = 10), HU (n = 10) and HU with RMF exposure (HU+RMF, n = 12) groups. Rats in the HU+RMF group were subjected to daily 2-hour exposure to moderate-intensity RMF (ranging from 0.60 T to 0.38 T) at 7 Hz for 4 weeks. HU caused significant decreases in body mass and soleus muscle mass of rats, which were not obviously altered by RMF. Three-point bending test showed that the mechanical properties of femurs in HU rats, including maximum load, stiffness, energy absorption and elastic modulus were not markedly affected by RMF. µCT analysis demonstrated that 4-week RMF did not significantly prevent HU-induced deterioration of femoral trabecular and cortical bone microarchitecture. Serum biochemical analysis showed that RMF did not significantly change HU-induced decrease in serum bone formation markers and increase in bone resorption markers. Bone histomorphometric analysis further confirmed that RMF showed no impacts on bone remodeling in HU rats, as evidenced by unchanged mineral apposition rate, bone formation rate, osteoblast numbers and osteoclast numbers in cancellous bone. Together, our findings reveal that RMF do not significantly affect bone microstructure, bone mechanical strength and bone remodeling in HU-induced disuse osteoporotic rats. Our study indicates potentially obvious waveform-dependent effects of electromagnetic fields-stimulated osteogenesis, suggesting that RMF, at least in the present form, might not be an optimal modality for inhibiting disuse osteopenia/osteoporosis.